The life and times of the Empress Wu Tse-t'ien of the T'ang dynasty - Guisso, RWL (1975)
The Life and Times of the Empress Wu Tse-t'ien of the T'ang Dynasty is an attempt to describe and place in perspective the régime of perhaps the most controversial ruler in the history of medieval China. It is an attempt also, to define an imperial vision, to show the shifting priorities and stages of policy by which the Empress Wu set out to achieve certain aims; and it offers comment on the successes and failures of her career. Within this context, the Empress herself emerges as a woman whose consistency of character and virtuosity of mind is reflected only palely in previous studies. Emphasis is placed in several areas. The first of these is the question of her position and her power. How did she win recognition as the legitimate sovereign of a state and a culture which had never before been ruled by a woman? And why, after this unique achievement, did she fail to preserve her position until her death? What influence did her unorthodox governmental role have upon the T'ang dynasty? And did her half-century of power leave any enduring marks upon China? Out of these considerations grows a second emphasis-- the tension between Confucian state-theory and the anomaly of a female ruler. In this clash, the tradition proved to be of greater flexibility than is generally recognized, but at the same time, proved to be so durable and so resilient that in the Chou, the Empress found herself increasingly frustrated and finally defeated by it. This study suggests that while husband or son occupied the throne, she was able to borrow their legitimacy and make great strides in the achievement of her two principal goals: the creation of a viable centralization, and of an imperial institution which would be free, secure, and supreme in its relationship with a new bureaucracy. In the Chou, however, the contemporary power structure came increasingly to resist innovation and with increasing success. As a result, the dynasty is best regarded as it was at the restoration, as a "caretaker" régime, a period of consolidation and continuity of policies initiated in the preceding quarter century. The Empress Wu seized the throne to preserve rather than to innovate. Continued in thesis ...